Scenarios for the future of the digital payment industry in Europe: exploration of strategic implications for the payment gateway provider paybyrd - Mrad, Selima (2023)
This work addresses changes in the European digital payment industry over the 10 years, with a focus on the potential implications of a Digital Euro for the Portuguese-Dutch payment gateway provider Paybyrd. Utilizing the Intuitive Logics School approach of scenario planning, four future scenarios were developed. Using the Ansoff Matrix, strategic options for Paybyrd were proposed, tailored to each scenario. The study emphasizes the need for Paybyrd's vigilance towards evolving trends and the importance of strategic adaptation to maintain competitiveness in a rapidly transforming industry. The work's results were crafted through extensive research and expert consultations via interviews and workshops.